Copyright Infringement on Twitter: The Unauthorized Use of K-Pop Fan Photography by Fanfiction Author Azzamine - Fairuzzaman, Fahmi; Almira, Sekar Diah Ayu (Prophetic Law Review, 2025)
Photographic works shared publicly on social media platforms, particularly Twitter, are not exempt from legal disputes, especially concerning copyright infringement. This research focuses on two central issues: first, the extent of copyright protection granted to photographs taken and uploaded by K-Pop fans on Twitter; and second, the legal remedies available to the rightful owners when their photographic works are used without permission. Using a normative legal research methodology, the study adopts a statutory approach, analyzing relevant legal rules and norms that apply to copyright protection. The research relies primarily on secondary legal sources, including laws, legal doctrines, journal articles, and relevant case studies. The findings indicate that photographic works shared via Twitter are protected under copyright law, which includes both moral rights—such as the right of attribution and integrity—and economic rights, including the right to reproduce and distribute the work. When such works are used without authorization, the original creators or rights holders have the option to pursue both litigation and non-litigation paths. Litigation may involve filing a civil or criminal case in the Commercial Court. Meanwhile, non-litigation solutions include various forms of alternative dispute resolution (ADR), such as mediation, arbitration, negotiation, conciliation, and consultation. This study highlights the legal vulnerabilities surrounding fan-created content in online spaces and underscores the importance of respecting copyright protections, even within fan communities. It also emphasizes the available legal pathways to protect the rights of content creators in digital environments.